Identifying the victims of workplace cyberbullying among lecturers - mirawati, ira; Suryana, Asep; Agustin, Herlina; Hidayat, Mien (Faculty of Communications Science, Dr. Soetomo University, 2019)
Cyberbullying exists not only among kids and teenagers but also adults. It takes place in many work sectors, including education. This research qualitatively investigated the victims of cyberbullying among lecturers. Thirty lecturers in West Java and Banten, fifteen males and fifteen females, were in-depth interviewed in this phenomenological research. Interviews were conducted by using a semi-structured guide. The results revealed that the victims were the â€œminorityâ€ of their group. They are unmarried young lecturers, lecturers with â€œnegativeâ€ physical condition, lecturers with unique or silly habits, male lecturers who feel â€œscaredâ€ of their wives, the â€œignoredâ€ lecturers, and young lecturers with unproductive working behaviour.